2011
DOI: 10.1016/j.cub.2011.02.032
|View full text |Cite
|
Sign up to set email alerts
|

Habitat Complexity Drives Experimental Evolution of a Conditionally Expressed Secondary Sexual Trait

Abstract: The conditional expression of alternative phenotypes underlies the production of almost all life history decisions and many dichotomous traits, including male alternative reproductive morphs and behavioral tactics. Changes in tactic fitness should lead to evolutionary shifts in developmental switch points that underlie tactic expression. We used experimental evolution to directly test this hypothesis by rearing ten generations of the male-dimorphic mite Rhizoglyphus echinopus in either simple or three-dimensio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
87
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(91 citation statements)
references
References 22 publications
4
87
0
Order By: Relevance
“…In R. echinopus, male dimorphism is environmentally cued by body size and male density (Radwan 2001;Tomkins et al 2011), and in a previous study we suggested that there is large genetic variation for the switch point that links male morph expression to the body size cue (Buzatto et al 2012). However, the heritability of switch point variation is constrained by the fact that male dimorphism is sex limited in its expression: genes that affect the switch point controlling male dimorphism are not expressed in females.…”
Section: Implications For the Et Modelmentioning
confidence: 96%
See 2 more Smart Citations
“…In R. echinopus, male dimorphism is environmentally cued by body size and male density (Radwan 2001;Tomkins et al 2011), and in a previous study we suggested that there is large genetic variation for the switch point that links male morph expression to the body size cue (Buzatto et al 2012). However, the heritability of switch point variation is constrained by the fact that male dimorphism is sex limited in its expression: genes that affect the switch point controlling male dimorphism are not expressed in females.…”
Section: Implications For the Et Modelmentioning
confidence: 96%
“…In contrast, scramblers' legs are all equally thin and without a sharp tip, and scramblers search for unguarded females to mate with (Radwan 1993;Radwan 2009). Male dimorphism in the bulb mite R. echinopus is environmentally cued by body size and male density (Radwan 2001;Tomkins et al 2011). …”
Section: Model Organismmentioning
confidence: 99%
See 1 more Smart Citation
“…Evolutionary changes in body size do sometimes track changes in thresholds of alternative male phenotypes [37,38], and this could just be due to frequency-dependent selection acting on male morphs [39]. However, across numerous island populations of these earwigs, it has previously been shown that the frequency of male morphs in the population varies widely due to changes in the position of the threshold relative to the body size distribution ( [40], see also [41]).…”
Section: Discussionmentioning
confidence: 99%
“…The closest to such a test was a study on the environmentally cued pupal colour dimorphism in butterflies [42], where the authors found no evidence for a correlation between the preference for green or brown pupation sites and the tendency to produce green or brown pupae. Similarly, by manipulating habitat complexity, an artificial selection experiment with bulb mites found that male body size and threshold responded to selection in opposing directions; increased habitat complexity caused lines to evolve towards smaller bodies, whereas the thresholds for major morph expression evolved towards larger bodies, both changes causing a decrease in the frequency of majors [37].…”
Section: Discussionmentioning
confidence: 99%